Women in academia: an analysis through a scoping review - Araneda-Guirriman, Carmen; Sepúlveda-Páez, Geraldy; Pedraja-Rejas, Liliana; San Martín, Julia (Frontiers in Education, 2023)
Changes in higher education, such as the performance measures in research, neoliberalism, the feminist movement, and the Covid-19 pandemic, have challenged women in academia. The incorporation of women in academia is a relatively recent phenomenon. It was only in the middle of the last century that the presence of women in higher education was systematically increasing; however, this increase in women's participation in Education has not eliminated gender gaps and inequalities. This article shows the results of a scoping review of the scientific literature, which aimed to identify what has been written about women's experiences in academia during the last decade and determine the knowledge gaps. To this end, three databases, Web of Science, Scopus, and Google Scholar, were reviewed for the literature search. As a result, 533 articles were obtained; however, after applying the exclusion criteria, 129 scientific papers were analyzed. The thematic analysis identified five central themes in the last ten years (difficulties experienced by women academics in their careers; the underrepresentation of women academics; the impact of neoliberalism on the careers of women academics; the facilitating factors in the careers of women academics; and the effect of Covid-19 pandemic on the careers of women academics). Finally, these categories and subcategories shape the challenges women academics face in higher Education and are analyzed and discussed.In conclusion, more than a third of the articles reviewed reflect on the difficulties experienced by female academics in their careers for the decade; however, during the last few years, it is possible to identify articles that address the challenges intensified in the context of the Covid-19 pandemic. As of 2018, articles addressing neoliberalism's effects on female academics' careers have increased. To a lesser extent, articles addressing aspects that facilitate the development of women's academic careers are also found. Thus, there is an essential reflection on the challenges and difficulties faced by women academics during their careers.